Renewing Cities. - Gittell, Ross J. (Princeton legacy library., 2014)
The cities of Lowell and New Bedford in Massachusetts, Jamestown in New York, and McKeesport in Pennsylvania have all undergone years of adversity and decline, their economic bases having been badly damaged by structural changes in the national economy, particularly in the manufacturing sector. In situations like these, can local development efforts make a difference? Ross Gittell answers in the affirmative. This interdisciplinary work focuses on comparative case studies of the four cities. The book reveals how public, private, and community-based local economic development initiatives affe.